Method to select gamma rays with energy above 50 GeV against a charge-particle background in the GAMMA-400 space telescope. Issue 3 (January 2016) - Kheymits, M D; Leonov, A A; Galper, A M; Kadilin, V; Arkhangelskaya, I V; Arkhangelskiy, A I; Gusakov, Yu V; Zverev, V G; Kaplin, V; Naumov, P Yu; Runtso, M F; Suchkov, S I; et al.
Abstract: Studying high-energy (>50GeV) cosmic gamma radiation raises a problem of selection of neutral gamma rays from a background of charged particles. The problem is embarrassed by the backsplash effect. The backsplash consists, in the main, of low-energy (1 MeV) secondary photons moving backwards and is produced by any high-energy gamma quantum. A charged-particle rejection method using the anticoincidence and time-of-flight systems is proposed. Charged-particle events are distinguished from those being triggered by high-energy gamma-rays producing backsplash. The method is based on the time separation of signals. It allows us to keep the gamma-ray detection efficiency high up to high energies.